2003
DOI: 10.1046/j.1538-7836.2003.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Venous thrombosis in children

Abstract: Summary.  Venous thromboembolic (VTE) events are being increasingly diagnosed in systemic and cerebral vessels in children. Systemic VTE are increasing in children as a result of therapeutic advances and improved clinical acumen in primary illnesses that previously caused mortality. The epidemiology of systemic VTE has been studied in international registries. In children older than 3 months, teenagers are the largest group developing VTE. The most common etiologic factor is the presence of central venous line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
129
1
11

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(143 citation statements)
references
References 140 publications
(180 reference statements)
2
129
1
11
Order By: Relevance
“…Recognizing that the overall prevalence of asymptomatic VTE in children with cancer is reported to be as high as 40%, 37 modalities used to diagnosis VTE in pediatrics include ultrasound, venography, computed tomography, and magnetic resonance imagining. 38 The role of D-dimer as a predictive tool in the diagnosis of VTE has not been validated in pediatric patients. 39 On the basis of the higher incidence of upper extremity VTE in the pediatric oncology population, generally associated with the use of a central venous catheter, an evidence-based recommendation for the detection of upper venous system thrombosis is available.…”
Section: Diagnostic Evaluation Of Thrombosismentioning
confidence: 99%
See 1 more Smart Citation
“…Recognizing that the overall prevalence of asymptomatic VTE in children with cancer is reported to be as high as 40%, 37 modalities used to diagnosis VTE in pediatrics include ultrasound, venography, computed tomography, and magnetic resonance imagining. 38 The role of D-dimer as a predictive tool in the diagnosis of VTE has not been validated in pediatric patients. 39 On the basis of the higher incidence of upper extremity VTE in the pediatric oncology population, generally associated with the use of a central venous catheter, an evidence-based recommendation for the detection of upper venous system thrombosis is available.…”
Section: Diagnostic Evaluation Of Thrombosismentioning
confidence: 99%
“…39 On the basis of the higher incidence of upper extremity VTE in the pediatric oncology population, generally associated with the use of a central venous catheter, an evidence-based recommendation for the detection of upper venous system thrombosis is available. 38 The PARKAA study concluded that both a venogram and ultrasound in combination were needed since venography was more sensitive than ultrasound in detecting intrathoracic (central) VTE, but ultrasound was more sensitive for internal jugular and axillary VTE. 40 There are limited data supporting the use of three-dimensional gadolinium-enhanced magnetic resonance imaging for detecting pediatric upper venous thrombosis; however, there have been no comparative studies with currently recommended ultrasound and venography to establish improved efficacy.…”
Section: Diagnostic Evaluation Of Thrombosismentioning
confidence: 99%
“…52 Thrombosis is also a common complication of central venous catheters in critically ill patients; in prospective studies, 53,54 the reported incidence has been up to 40%. Current treatment recommendations suggest short-term prophylactic anticoagulation as an option for children who are in high-risk situations (immobility, major surgery, or trauma) and have 3 or more acquired risk factors.…”
Section: Deep-vein Thrombosis Prophylaxismentioning
confidence: 99%
“…Current treatment recommendations suggest short-term prophylactic anticoagulation as an option for children who are in high-risk situations (immobility, major surgery, or trauma) and have 3 or more acquired risk factors. 52 The risk-benefit ratio should be considered for each patient. 52 The goal of this element of the checklist is to highlight the need to consider each patient's individual risk factors for venous thromboembolic events.…”
Section: Deep-vein Thrombosis Prophylaxismentioning
confidence: 99%
See 1 more Smart Citation